SOSIALISASI PROGRAM CSR OLEH PUBLIC RELATIONS PT BUMI SUKSESINDO TUMPANG PITU SUMBERAGUNG PESANGGARAN - Maskur Maskur; Ali Mabrur; Krismun Krismun (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study discusses how the socialization of the CSR program of PT. Bumi Suksesindo in introducing UKM products through a boarding school community care event, because SME products are not fully known to the wider community. The purpose of this research is to know the socialization strategy of PT Bumi Suksesindo's CSR program through the pesantren community. This study uses the theory of symbolic interaction. The paradigm used is constructivism with a qualitative research approach. The method used is a case study. The research subjects in this study consisted of key informants and informants. Data collection techniques using interviews, observation and documentation. The results of this study indicate that the socialization process that has been carried out by public relations PT Bumi Suksesindo in serving with face-to-face activities directly to the external public. Where in the event you can promote your own business, so that the wider community can find out about PT Bumi Suksesindo's CSR program and interact in the event.